Intercalation of fullerite C₆₀ with N₂ molecules. An investigation by x-ray powder diffraction - Galtsov, N.N.; Prokhvatilov, A.I.; Dolgova, G.N.; Cassidy, D.; Gadd, G.E.; Moricca, S.; Sundqvist, B. (Физика низких температур, 2007)
The lattice parameter a of fullerite C₆₀ intercalated with N₂ molecules is investigated in the temperature
interval 6–295 K by x-ray diffraction. It is found that the interstitial molecular N₂ has a considerable effect
on both the temperatures, Tc of the orientational phase transition and Tg of the orientational glass formation.
Hysteresis of a(T) has been detected in the Tc and Tg regions, besides, the abrupt change in the volume over
the region defining Tc. Complete intercalation of C₆₀ with N₂ molecules results in a 0.2% increase in the lattice
parameter, which persists over the whole temperature range. Evidence is also obtained that the interstitial
guest molecular N₂ induces a slight deformation of the cubic symmetry of the host C₆₀ lattice.